2014
DOI: 10.3758/s13421-014-0405-2
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific prospective-memory processing: Evidence for flexible attention allocation adjustments after intention encoding

Abstract: Prospective memory (PM) is remembering to fulfill intentions in the future. Interference of unfulfilled intentions with ongoing activities reflects the allocation of attention to the PM task. Prior research has shown that, when people know in which specific context PM cues will occur, attention allocation is adaptive, with slower responses in the PM-relevant context. We examined whether people flexibly adjust their attention allocation when the PM-context association is unknown at intention encoding and must b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
42
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 13 publications
8
42
3
Order By: Relevance
“…Of particular interest was the finding that a cue-driven monitoring process was directly initiated by subtle cues, in the form of semantically related images that were embedded in the continuous task. Past studies have revealed that contextual cues in the environment often prompt retrieval of a future intention (Harris & Wilkins, 1982, Henry et al, 2012Kuhlmann & Rummel, 2014;Kvavilashvilli & Fisher, 2007), and the present research extended this finding with the observation that contextual cues can trigger retrieval of the future intention, thereby prompting participants to overtly monitor for prospective memory targets. Salient external cues have been shown to be helpful to adults (Guajardo & Best, 2000) in a variety of laboratory studies (Einstein & McDaniel, 1996;Kim & Mayhorn, 2008;Villa, 1998), including investigations of air traffic control (Loft et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Of particular interest was the finding that a cue-driven monitoring process was directly initiated by subtle cues, in the form of semantically related images that were embedded in the continuous task. Past studies have revealed that contextual cues in the environment often prompt retrieval of a future intention (Harris & Wilkins, 1982, Henry et al, 2012Kuhlmann & Rummel, 2014;Kvavilashvilli & Fisher, 2007), and the present research extended this finding with the observation that contextual cues can trigger retrieval of the future intention, thereby prompting participants to overtly monitor for prospective memory targets. Salient external cues have been shown to be helpful to adults (Guajardo & Best, 2000) in a variety of laboratory studies (Einstein & McDaniel, 1996;Kim & Mayhorn, 2008;Villa, 1998), including investigations of air traffic control (Loft et al, 2011).…”
Section: Discussionsupporting
confidence: 65%
“…It remains unclear exactly how environmental cues interact with the cognitive mechanisms supporting prospective memory, although some research has suggested that people will adjust how they allocate attention to the prospective memory task if they are instructed about contextual cues that will accompany the prospective memory target (Kuhlmann & Rummel, 2014). Scullin, McDaniel, and Einstein (2010) examined this question by implanting subtle cues (either words that were semantically related to the prospective memory target or specific color backgrounds) proximal to the onset of that target item.…”
mentioning
confidence: 99%
“…As reviewed by Smith and Loft (2014), studies that have demarcated clearly the blocks of trials which contain a PM target event from those that will not include a PM target find no cost to ongoing performance unless the context is relevant for a PM response (Cook, Marsh, Clark-Foos, & Meeks, 2007; Marsh, Hicks, & Cook, 2006). Other studies have found a cost on irrelevant trials, albeit often reduced from relevant trials, but in those studies the context is less predictive of the appearance of a PM target because in many cases the relevant and irrelevant trials alternated randomly so that it was not possible to predict in advance of the presentation of the stimulus on a given trial whether the particular trial would be relevant (Cohen, Jaudas, Hirschhorn, Sobin, & Gollwitzer, 2012; Kuhlmann & Rummel, 2014; Lourenço & Maylor, 2014; Lourenço, White, & Maylor, 2011; Marsh, Cook, & Hicks, 2006, Experiment 1B). Additional details can be found in Table 1 of Smith and Loft (2014; Smith, under review).…”
Section: Prospective Memory In Context: Moving Through a Familiar Spacementioning
confidence: 99%
“…One factor that may influence the process of finding a missing/wanted person is the searcher's expectations of encountering the person. PM research shows that people allocate their limited cognitive resources according to their expectations about when they will need to use their resources to complete a PM task (Cook, Marsh, & Hicks, ; Kuhlmann & Rummel, ; Lourenço & Maylor, ; Lourenço, White, & Maylor, ; Marsh, Hicks, & Cook, ; Smith, Hunt, & Murray, ). In one study, Cook et al () told participants to expect a PM cue to appear during the time that it actually appeared or to expect a PM cue to appear after it actually appeared.…”
Section: Introductionmentioning
confidence: 99%
“…Participants with accurate expectations performed better than participants with inaccurate expectations. In another study, Kuhlmann and Rummel () told some participants to expect PM cues after a specific shape (e.g., triangle) appeared on a computer screen. Others were told that the PM cues would appear after a shape but were not told which shape.…”
Section: Introductionmentioning
confidence: 99%